2021
DOI: 10.12669/pjms.37.7.4355
|View full text |Cite
|
Sign up to set email alerts
|

Perceived effectiveness of learning methods among preclinical medical students - role of personality and changes over time

Abstract: Background and Objectives: Active learning methods are vital in inculcating skills of critical thinking, lifelong learning and effective communication. Personality may influence learning method preferences and academic performance. The aim of this cross sectional study was to examine the relationship between students’ personality and their predilection for learning methods and academic performance. Methods: Perceived effectiveness of learning methods was assessed over time. Second- and third-year medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…In this case study, utilizing the preceptor model coupled with extensive didactic training and an applied research project appeared to aid in the completion of undergraduate collegiate degrees and pursual of further graduate education among students from both private and public institutions. The value of the preceptor and didactic model was consistent with the broader literature (Arain et al, 2021; Kantar, 2021), yet trainees’ feedback about VA-CERP suggests that additional unique elements of this program aided in their professional development including didactic training on the value of mental health research, clinical practice, public policy, and veteran care. Findings from this case study are consistent with extant literature highlighting the benefits of undergraduate mentorship and extracurricular research training and extending them to VHA where research on undergraduate programs has been limited.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In this case study, utilizing the preceptor model coupled with extensive didactic training and an applied research project appeared to aid in the completion of undergraduate collegiate degrees and pursual of further graduate education among students from both private and public institutions. The value of the preceptor and didactic model was consistent with the broader literature (Arain et al, 2021; Kantar, 2021), yet trainees’ feedback about VA-CERP suggests that additional unique elements of this program aided in their professional development including didactic training on the value of mental health research, clinical practice, public policy, and veteran care. Findings from this case study are consistent with extant literature highlighting the benefits of undergraduate mentorship and extracurricular research training and extending them to VHA where research on undergraduate programs has been limited.…”
Section: Discussionsupporting
confidence: 63%
“…The goal of the VA Center of Excellence Research Program (VA-CERP) is to provide motivated undergraduates striving to become future health care providers with quality mental health research experience and professional development. VA-CERP includes empirically supported components that promote undergraduate success and the transition to graduate school, including tiered mentorship (Burgess et al, 2018;Zaniewski & Reinholz, 2016), a didactic-preceptor model (Arain et al, 2021;Kantar, 2021), handson experience (Seymour et al, 2004;Stohr-Hunt, 1996), and participation on interdisciplinary teams (Aldriwesh et al, 2022;Spaulding et al, 2021), strongly aligning with several proposed solutions identified by the CCTC (2021). The tiered mentorship model embedded in our program affords our undergraduate students several sources of mentorship, ranging from midcareer doctoral level mentors, advanced postdoctoral fellows, and bachelor's and master's level preceptors, guiding students in developing their graduate school applications, composing personal statements, and interviewing for positions.…”
mentioning
confidence: 99%
“…The results showed that some students who are sensitive and tend to avoid conflict and confrontation preferred nearly equally both traditional lectures and TBL. 41 In the current study, it was surprising to find that approximately twice as many students preferred TBL over seminars, although their achievements in seminars were acceptable. Seminars are subject-centered or leader-centered, rather than participant-centered.…”
Section: Discussionmentioning
confidence: 59%